Overload in Immigration Detention Houses - M. Ridwan Ari Hermawan; Devina Yuka Utami (Journal of Law and Border Protection, 2020)
Implementation of Standard Operating Procedure for Immigration Detention Center (Rudenim) is still not running smoothly or less effective. This is due to the confusion and contradictions in the statement of basic measures and policy objectives which have resulted in disciplinary regulations that intersect with Standard Operating Procedures regarding temporary exit permits for Deteni without escort. The level of supervision carried out by Rudenim is not optimal. The existing regulations have not been able to provide effective supervision so that violations may occur. If there is no current supervision of asylum seekers outside the shelter, it is possible that other bad things will happen, so there is a need for a good formulation of the Code of Conduct. And also the lack of rudenim at the Immigration Office in Indonesia which causes overload, resulting in unwanted cases.